1988
DOI: 10.1139/m88-140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ascorbate on oxygen uptake and growth of Escherichia coli B

Abstract: The addition of ascorbate to aerobically growing cultures of Escherichia coli B caused only a short pause in growth and no subsequent change in the rate or extent of growth. The effect of ascorbate on oxygen uptake varied from inhibition in minimal medium to stimulation in rich medium. Cyanide-resistant growth and oxygen uptake were stimulated by ascorbate. Both the rate and extent of anaerobic growth were stimulated in proportion to the amount of ascorbate added when fumarate was the terminal electron accepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…SgaT proved not to be homologous to any functionally characterized protein. Two possibilities were considered: (i) SgaT-SgaB-SgaA could be a novel type of enzyme II complex, or (ii) SgaT could be a secondary transporter, while SgaA and SgaB might regulate expression of the sga operon or the activity of one or more of its gene products (18,25).It has been known for over 60 years that various bacteria, including E. coli, can ferment L-ascorbate (L-xyloascorbate [vitamin C]) under anaerobic but not aerobic conditions (7,19,32). The unstable hydrolysis product of L-ascorbate, 3-keto-Lgulonate, has been implicated as an intermediate in its catabolism (28).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…SgaT proved not to be homologous to any functionally characterized protein. Two possibilities were considered: (i) SgaT-SgaB-SgaA could be a novel type of enzyme II complex, or (ii) SgaT could be a secondary transporter, while SgaA and SgaB might regulate expression of the sga operon or the activity of one or more of its gene products (18,25).It has been known for over 60 years that various bacteria, including E. coli, can ferment L-ascorbate (L-xyloascorbate [vitamin C]) under anaerobic but not aerobic conditions (7,19,32). The unstable hydrolysis product of L-ascorbate, 3-keto-Lgulonate, has been implicated as an intermediate in its catabolism (28).…”
mentioning
confidence: 99%
“…It has been known for over 60 years that various bacteria, including E. coli, can ferment L-ascorbate (L-xyloascorbate [vitamin C]) under anaerobic but not aerobic conditions (7,19,32). The unstable hydrolysis product of L-ascorbate, 3-keto-Lgulonate, has been implicated as an intermediate in its catabolism (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with results obtained by other investigators. Richter et al (1988) reported that addition of ascorbate to aerobically growing cultures of E. coli B caused only a short pause in growth, and no subsequent change in the rate of growth. Tabak et al (2003) reported that 10-20 mg/ ml ascorbic acid inhibited Helicobacter pylori growth under microaerophilic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Based on computational docking of the L-xylulose 5-phosphate substrate to UlaE and structural similarities of the active site of this enzyme to the active sites of other epimerases, a metal-dependent epimerization mechanism for UlaE is proposed, and Glu155 and Glu251 are implicated as catalytic residues. Mutation and activity measurements for structurally equivalent residues in related epimerases supported this mechanistic proposal.It has been known for nearly 70 years that various bacteria, including Escherichia coli, can ferment L-ascorbate (vitamin C) under anaerobic conditions (2,10,30,40). This process has been demonstrated to involve proteins encoded by two divergently transcribed operons, the ulaGR and ulaABCDEF operons (3,40,44).…”
mentioning
confidence: 99%